2022
DOI: 10.1007/s00414-022-02852-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the potential of morphological parameters for human dental identification: part 3—selecting the strongest skeletal identifiers in the mandible

Abstract: The current study aimed to select the best mandibular morphological identifiers.One hundred eighty-five panoramic radiographs were retrospectively collected, in which four landmarks were located on the mandible: the most superior point of the condyle right/left (CONR/L), of the coronoid right/left (CORR/L), of the mandibular lingula right/left (LINR/L), and the most mesial point of the mental foramen right/left (MMFR/L). Five linear measurements, 6 angles and 10 ratios were measured bilaterally. Three groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A few studies are available regarding some of these indices, such as the study by Iliescu et al [ 23 ], who assessed several linear, angular, and relative parameters in the mandible and showed their high potential for gender determination. Rad et al [ 18 ] evaluated some of these factors in an Iranian population and found that all of them were significantly different between males and females, including the gonial angle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies are available regarding some of these indices, such as the study by Iliescu et al [ 23 ], who assessed several linear, angular, and relative parameters in the mandible and showed their high potential for gender determination. Rad et al [ 18 ] evaluated some of these factors in an Iranian population and found that all of them were significantly different between males and females, including the gonial angle.…”
Section: Discussionmentioning
confidence: 99%
“… Distance between the superior border of the mental foramen and the inferior border of the ramus ( Figure 1 H) [ 22 ]. Distance between the inferior border of the mental foramen and the inferior border of the ramus ( Figure 1 I) [ 23 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation